The impact of maternal mood and economic stress during Covid-19 pandemic on infant behaviour: Findings from the cross-sectional UK Covid-19 New Mum Study. - Adriana Vázquez-Vázquez; Emeline Rougeaux; Sarah Dib; Mary Fewtrell; Jonathan C Wells (Public Library of Science (PLoS), 2024)
The UK Covid-19 New Mum Study (cross-sectional study) recorded maternal experience during the early stages of the pandemic. Our previous analyses showed that the pandemic and 2020 national lockdown negatively impacted maternal mental health. Here, we describe changes in infant behaviour (crying and fussiness) reported by the mother during the Covid-19 pandemic compared to beforehand, and test whether these changes are associated with maternal variables (mental health, coping, financial insecurity, income and household support). We included only responses of mothers whose infants were born before the pandemic started (n = 2,031). Composite scores for maternal mental health and coping were obtained using principal components analysis. Multivariable logistic regression analysis was used to test whether maternal mood and coping and household financial stresses were associated with changes in infant behaviour considered negative (becoming fussier, crying more). Adjusting for confounders, the odds of the infant being fussier and crying more increased by 52% (OR = 1.52, 95% CI = 1.35;1.72) and 64% (OR = 1.64, 95% CI = 1.38;1.95), respectively, if the mother experienced poorer mental health. If the mother coped better and had more time to focus on her health and interests, the odds of these outcomes decreased by 27% (OR = 0.73, 95% CI = 0.65;0.83) and 23% (OR = 0.77, 95% CI = 0.65;0.91), respectively. Mothers who reported that, during the lockdown, household chores were more equally divided 'to a high extent' had 40% (OR = 0.60, 95% CI = 0.39;0.92) lower odds of reporting that their babies became fussier. Reporting major/moderate impact on food expenses was associated with the infant crying more (OR = 2.52, 95% CI = 1.16;5.50). Our results are consistent with previous studies showing that maternal wellbeing plays a significant role in children's behavioural changes during lockdowns. We need strategies to improve mental health and enable women to develop the skills to maintain resilience and reassure their children in challenging times.